Mechanisms underlying the anti-aging activity of bergamot (Citrus bergamia) extract in human red blood cells - Remigante, Alessia; Spinelli, Sara; Straface, Elisabetta; Gambardella, Lucrezia; Russo, Marina; Cafeo, Giovanna; Caruso, Daniele; Falliti, Giuseppe; Dugo, Paola; Dossena, Silvia; Marino, Angela; Morabito, Rossana (Frontiers in Physiology, 2023)
Aging is a process characterised by a decline in physiological functions. Reactive species play a crucial role in the aging rate. Due to the close relationship between aging and oxidative stress, functional foods rich in phytochemicals are excellent candidates to neutralise age-related changes. This investigation aims to verify the potential protective role of bergamot (Citrus bergamia, Femminello cultivar) peel and juice extract in a model of aging represented by human red blood cells (RBCs) exposed to D-Galactose (D-Gal). Bergamot peel and juice extracts were subjected to RP-HPLC/PDA/MS for determination of their composition in bioactive compounds. Markers of oxidative stress, including ROS production, thiobarbituric acid reactive substances (TBARS) levels -a marker of lipid peroxidation, oxidation of total protein sulfhydryl groups, as well as the expression and anion exchange capability of band 3 and glycated haemoglobin (A1c) production have been investigated in RBCs treated with D-Gal for 24 h, with or without pre-incubation for 15 min with 5 µg/mL peel or juice extract. In addition, the activity of the endogenous antioxidant system, including catalase (CAT) and superoxide dismutase (SOD), as well as the diversion of the RBC metabolism from glycolysis towards the pentose phosphate pathway shunt, as denoted by activation of glucose-6-phosphate dehydrogenase (G6PDH), have been explored. Data shown here suggest that bergamot peel and juice extract i) prevented the D-Gal-induced ROS production, and consequently, oxidative stress injury to biological macromolecules including membrane lipids and proteins; ii) significantly restored D-Gal-induced alterations in the distribution and ion transport kinetics of band 3; iii) blunted A1c production; iv) effectively impeded the over-activation of the endogenous antioxidant enzymes CAT and SOD; and v) significantly prevented the activation of G6PDH. These results further contribute to shed light on aging mechanisms in human RBCs and identify bergamot as a functional food rich in natural antioxidants useful for prevention and treatment of oxidative stress-related changes, which may lead to pathological states during aging.